2020
DOI: 10.1111/jonm.13112
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional observational study of missed nursing care in hospitals in China

Abstract: Patient safety is a priority in health service delivery, and nurses play a critical role in every stage of direct patient care and adverse incident minimization (WHO, World Health Organization, 2019). The primary nursing-related threats to patient safety are errors of commission and missed nursing care (MNC)-an omission error (Kalisch & Xie, 2014): the former may result in medical errors or malpractice, while the latter is often rationalized and, consequently, left unresolved (Jones, Hamilton, & Murry, 2015). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 29 publications
(57 reference statements)
0
21
0
15
Order By: Relevance
“…An item with an average score > 3.03 indicates low job satisfaction. The Chinese version of the McCloskey/Mueller Satisfaction scale has been widely used and has demonstrated satisfactory reliability and validity for the Chinese sample [ 27 , 28 ], and the Cronbach’s α in this study was 0.97.…”
Section: Methodsmentioning
confidence: 87%
“…An item with an average score > 3.03 indicates low job satisfaction. The Chinese version of the McCloskey/Mueller Satisfaction scale has been widely used and has demonstrated satisfactory reliability and validity for the Chinese sample [ 27 , 28 ], and the Cronbach’s α in this study was 0.97.…”
Section: Methodsmentioning
confidence: 87%
“…Consistent with several previous studies, giving emotional support is still one of the most frequent care items to be missed, although in this study we found an even greater proportion compared to the previous studies. 5,33 The high work demand in the NICU left the nurses with little time to do their tasks, this sometimes lead them to postpone some tasks deemed to be less "important", such as the psycho-social task including giving emotional support to the parents and/or family of the neonates. 34,35 Regarding bedside glucose monitoring, other studies presented opposite results, in which bedside glucose monitoring is part of the least frequent care to be missed.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with several previous studies. 5,33,35,36 Although labor resources hold the biggest portion in contributing to missed nursing care, interventions that exclusively focus on labor resources may not be enough to decrease the incidence of missed nursing care. 4 Intervention to ensure better teamwork, communication, as well as less excessive workload, better personnel deployment, and better flows in patient acuity and volume is needed to minimize the incidence of missed nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…Missed nursing care has been measured using either direct observational methods or subjective patient and nurse reporting of care that is missed 1 , 8 , 9 . Results of studies on missed nursing care are also frequently presented in different formats, as either the proportion of care that is missed or as a mean/median score when a Likert scale is used 22 , 28 , 29 . To describe the most frequently missed categories of missed nursing care, we will report either of these estimates and rank order them to identify the three most and least frequently missed nursing care categories.…”
Section: Protocolmentioning
confidence: 99%